Peace Education And National Security: The Need For Its Improvement In Nigerian Schools (Texas Journal of Multidisciplinary Studies, 2023)
This study delves into the interrelationship between peace education and national security, emphasizing the urgency to enhance it within Nigerian educational institutions. This urgency is heightened due to the prevalent security challenges in Nigeria that serve as barriers to the nation's development trajectory. The paper provides an in-depth exploration of key concepts, including peace, national security, education, and peace education, elaborating on their inherent challenges and anticipated outcomes. The system theory framework was employed to elucidate the symbiotic relationship between peace education and national security. Drawing from both published and unpublished secondary sources, this position paper employed a thematic content analysis approach for data examination. Upon assessing the connection between peace education and Nigeria's national security, the study discerned that enhancing peace education can foster respect for all life forms, promote non-violence, advocate for justice through understanding and persuasion, and encourage communal sharing, tolerance, and unity. However, the research also identified several impediments to the successful integration of peace education. These include the government's hesitancy in fully embracing peace education, financial constraints, and the absence of a comprehensive and relevant peace education curriculum. To address these challenges, the paper puts forth several recommendations. Foremost among these is the call for the Nigerian Government to prioritize the augmentation of peace education within the school curriculum. This enhancement should be harmonized with entrepreneurship education across all educational tiers. Such an initiative would not only inculcate the importance of skill acquisition for societal sustenance in students but would also foster the development of their psycho-motor domain. The emphasis here is that equipping students with both food and skills can potentially curb criminal activities, especially since a significant portion of criminal acts is committed by unemployed youths